Digital Revolution Tamed The Case of the Recording Industry - Sun, Hyojung; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book explores why widespread predictions of the radical transformation in the recording industry did not materialise. Although the growing revenue generated from streaming signals the recovery of the digital music business, it is important to ask to what extent is the current development a response to digital innovation. Hyojung Sun finds the answer in the detailed innovation process that has taken place since Napster. She reassesses the way digital music technologies were encultured in complex music valorisation processes and demonstrates how the industry has become reintermediated rather than disintermediated. This book offers a new understanding of digital disruption in the recording industry. It captures the complexity of the innovation processes that brought about technological development, which arose as a result of interaction across the circuit of the recording business - production, distribution, valorisation, and consumption. By offering a more sophisticated account than the prevailing dichotomy, the book exposes deterministic myths surrounding the radical transformation of the industry.
List of Figures -- List of Tables -- List of Abbreviations -- Chapter 1 Introduction -- Chapter 2 Towards a More Sophisticated Account -- Chapter 3 The History of Technological Development in the Recording Industry -- Chapter 4 Evolution of Digital Music Services -- Chapter 5 Case Study - Spotify -- Chapter 6 Digital Music Distribution Networks -- Chapter 7 Case Study - INgrooves -- Chapter 8 Digital Revolution Tamed in the Recording Industry -- Bibliography.
Keywords: Science -- Social aspects; Music; Information technology -- Law and legislation; Mass media -- Law and legislation; Digital media; Science and Technology Studies; Music; IT Law, Media Law, Intellectual Property; Digital and New Media